POTENSI POHON AREN (Arenga pinnata) DI DESA HATUSUA KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Dwi Yulia Saputri; Ludia Siahaya; Moda Talaohu (MARSEGU : Jurnal Sains dan Teknologi, 2026)
This study aimed to determine the potential of sugar palm (Arenga pinnata) and its utilization by the community in Hatusua Village, Kairatu District, West Seram Regency. Sugar palm is one of the palm species with high economic and ecological value, as nearly all parts of the tree can be utilized. The research employed a combination of strip-plot methods for vegetation analysis and a census method to assess community utilization of sugar palm. The results showed that Arenga pinnata was the dominant species with an Important Value Index (IVI) ranging from 239.89 to 296.44 across all observation plots. Based on interview results, the community primarily utilizes sugar palm for the production of palm sugar, sap, kolang-kaling, palm fiber, and traditional building materials. Ecologically, sugar palm plays an important role in maintaining slope stability and preventing erosion. Given its significant economic and ecological potential, sugar palm in Hatusua Village has considerable opportunity to be developed through a sustainable agroforestry system involving the participation of the local community.